Delta-like 1 homolog (DLK1) as a possible therapeutic target and its application to radioimmunotherapy using 125I-labelled anti-DLK1 antibody in lung cancer models (HOT1801 and FIGHT004). (March 2021) - Takagi, Hironori; Zhao, Songji; Muto, Satoshi; Yokouchi, Hiroshi; Nishihara, Hiroshi; Harada, Toshiyuki; Yamaguchi, Hikaru; Mine, Hayato; Watanabe, Masayuki; Ozaki, Yuki; Inoue, Takuya; Yamaura, Takumi; et al.
Highlights: DLK1 is a member of the Notch ligand family such as delta-like 3 (DLL3). DLK1 is expressed in a subset of both small-cell lung cancer (SCLC) and non-small-cell lung cancer (NSCLC). DLK1 expression could be a predictor for metastasis and postoperative recurrence in NSCLC. DLK1 could be a new therapeutic target and lead to the development of alpha-particle radioimmunotherapy for SCLC. Abstract: Objectives: Delta-like 1 homolog (DLK1) is a non-canonical Notch ligand known to be expressed in several cancers but whose role in lung cancer is not yet fully understood. We sought to confirm DLK1 expression in small-cell lung cancer (SCLC) and non-small-cell lung cancer (NSCLC), and to examine DLK1's clinical significance. Furthermore, we examined the possible utility of DLK1 as a novel target in radioimmunotherapy (RIT). Methods: We retrospectively assessed the correlation between clinical features and DLK1 expression by immunohistochemistry in resected specimens from 112 patients with SCLC and 101 patients with NSCLC. Moreover, we performed cell and animal experiments, and examined the possibility of RIT targeting DLK1 in SCLC using iodine-125 ( 125 I) -labeled anti-DLK1 antibody, knowing that 125 I can be replaced with the alpha-particle-emitter astatine-211 ( 211 At). Results: In SCLC and NSCLC, 20.5 % (23/112) and 16.8 % (17/101) of patients (respectively) had DLK1-positive tumors. In NSCLC, DLK1 expression was associated with recurrence-free survival (P < 0.01) but not with overall survival. In SCLC, there was no association between DLK1 expression and survival. In addition, 125 I-labeled anti-DLK1 antibody specifically targeted DLK1 on human SCLC tumor cell lines. Furthermore, 125 I-labeled anti-DLK1 antibody was incorporated into tumor tissue in a mouse model. Conclusion: A proportion of SCLC and NSCLC exhibits DLK1 expression. As a clinical feature, DLK1 expression could be a promising prognostic factor for recurrence in patients with resected NSCLC. In addition, DLK1 could serve as a new therapeutic target, including RIT, as suggested by our pilot study using a radiolabeled anti-DLK1 antibody in SCLC.